Implementasi Kepemimpinan Kepala Sekolah dengan Budaya Organisasi terhadap Kinerja Guru - Afrida , Yanti; Fitri , Hayati (Journal of Educational Management Research, 2022)
Teacher performance is the behavior of a person who produces certain work results after fulfilling a number of requirements. Where teacher performance is strongly influenced by organizational culture. The stronger the orientation of cultural values such as views on work life, time, and ethics or values will influence the behavior that has an impact on improving teacher performance. Organizational culture is an understanding of the values and norms that are important in the organization that guide behavior organizational members or developed in learning to overcome problems of external adaptation and internal integration. With an organizational culture, all school personnel will carry out tasks organization based on prevailing values and norms. If the organizational culture is good, the teacher's work will automatically have a good impact. For this reason, the role of the school principal and special efforts are needed in developing organizational culture as a value system that is understood, imbued, carried out jointly by members of the organization as a system of meaning or guidelines for organizational actors. Because the school principal's leadership is very influential, because it can give authority to influence, move and direct action and encourage the emergence of a strong will with enthusiasm and confidence for teachers, staff and students in carrying out their respective tasks for the sake of progress and provide inspiration for the school.